Perception towards waqf management in Johor Bahru / Nor Syahira Ismail - Ismail, Nor Syahira (Faculty of Business Management, 2016)
Waqf property effective management will be able to generate positive and beneficial to the beneficiary or recipient. There are some issues that have been encountered by the Administration in dealing with the property of the Waqf (Mohd Puad, Jamlus Rafdi, & Shahar, 2014). This research is done to see the relationship between knowledge on Waqf and perception towards Waqf management in Malaysia focusing in Johor Bahru. This research will also be conduct to determine the relationship between understanding on the concept of Waqf and perception towards Waqf management in Malaysia focusing in Johor Bahru. By doing this research, we also want to know the relationship between importance of Waqf for society and perceptions towards Waqf management. The independent variables used in this study are knowledge on Waqf, understanding on the concept of Waqf and importance of Waqf for society, while the dependent variable is perceptions towards Waqf management. The methods that will be used in this research is SPSS and Johor Bahru was chosen as the targeted location in conducting this research study and data will be collected by using the questionnaire and it will be distributed to the small population of Muslim communities in Johor Bahru. The questionnaire is distributed is to find the answer about public perception towards Waqf management. Through suggestions and opinions from this research, hopefully, the proceeds from the management of waqf property in Malaysia can be fully optimized and public became more aware about Waqf. Keywords :Waqf, Waqf management, public’s perception towards Waqf management